التدريب الدعوي في ضوء السنة النبوية دراسة تأصيلية - مداني, فوزية; بوعافية, عيسى (جامعة الوادي - University of Eloued, 2022)
في دراستنا لموضوع" التدريب الدعوي في ضوء السنة النبوية" انطلقنا من إشكالية وهي أن هناك من يرى أن علم الإدارة عامة والتدريب خاصة علم جديد، غربي المنبت، وأنّه -صلى الله عليه وسلّم – لم يمارسه، وفي ضوء ذلك كان السؤال الرئيس للدراسة هو: هل درّب النبي  الصحابة على الدعوة ؟وما هي معالم هذا التدريب؟ وللإجابة على هذا التساؤل تم استخدام المنهج الاستنباطي التحليلي مع الاستعانة بالمنهج الاستقرائي، وقد توصلت الدراسة إلى مجموعة من النتائج كان من أهمها:أنّ التدريب ليس وليد العصر،بل سبق الإسلام الأمم الأخرى في الأخذ به والحث عليه ويظهر ذلك جليا في اهتمام النبي بتدريب الدعاة. وقد تخرج من هذه المدرسة المحمدية نماذج رائدة من الدعاة نشروا الدعوة في أرجاء المعمورة. In our study topic ‘Advocacy training in the light of the Sunnah’, we started up from the hypothesis that some consider that Management science, in general and coaching specifically is a new science of Western descent and that Mohammed (peace and bless be upon him) didn’t practise it. That’s why the leading question of the study has been: Did Prophet Mohammed train his companions on advocacy? And what are the features of this training? And to answer this question the analytical deductive method has been used referring also to the inductive method. The study has come out with a series of results; the utmost important were that coaching was not initiated in this Age, butIslam preceded the other nations and has already adopted it and urged it; and this is clear in the importance the Prophet gave to coaching preachers. Pioneer models of preachers came out of Mohammed’s school who spread advocacy all over the world.
Advocacy training in the light of the Sunnah
مقال
Keywords: الدعوة، التدريب، السنة النبوية; Daewa,training, Sunnah